2018
DOI: 10.1186/s12917-018-1403-6
|View full text |Cite
|
Sign up to set email alerts
|

Tick- and fly-borne bacteria in ungulates: the prevalence of Anaplasma phagocytophilum, haemoplasmas and rickettsiae in water buffalo and deer species in Central Europe, Hungary

Abstract: BackgroundHunting constitutes an important industry in Europe. However, data on the prevalence of vector-borne bacteria in large game animal species are lacking from several countries. Blood or spleen samples (239 and 270, respectively) were taken from red, fallow and roe deer, as well as from water buffaloes, mouflons and wild boars in Hungary, followed by DNA extraction and molecular analyses for Anaplasma phagocytophilum, haemoplasmas and rickettsiae.ResultsBased on blood samples, the prevalence rate of A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
4
27
2
Order By: Relevance
“…Whereas none of the blood samples from the water buffaloes tested positive for R. helvetica or other rickettsiae, R. helvetica was detected in a blood sample and a spleen sample from a deer. Moreover, a deer spleen sample also tested positive for an unknown Rickettsia [44]. A recent study in Cameroon showed the successful detection of Rickettsia in cattle using conventional PCR targeting the 16s rDNA gene, with a prevalence of 14.3% [45].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Whereas none of the blood samples from the water buffaloes tested positive for R. helvetica or other rickettsiae, R. helvetica was detected in a blood sample and a spleen sample from a deer. Moreover, a deer spleen sample also tested positive for an unknown Rickettsia [44]. A recent study in Cameroon showed the successful detection of Rickettsia in cattle using conventional PCR targeting the 16s rDNA gene, with a prevalence of 14.3% [45].…”
Section: Discussionmentioning
confidence: 97%
“…The same reason may explain the negative results obtained in this study. A study on the detection of vector-borne pathogens, including Rickettsia in ungulates in Hungary, was conducted using real-time PCR targeting 23S rRNA and gltA for R. helvetica and other Rickettsia, respectively [44]. Whereas none of the blood samples from the water buffaloes tested positive for R. helvetica or other rickettsiae, R. helvetica was detected in a blood sample and a spleen sample from a deer.…”
Section: Discussionmentioning
confidence: 99%
“…Although no studies have evaluated the potential for white-tailed deer to become bacteremic with R. amblyommatis , other Rickettsia spp. have been detected in the blood of cervids 4851 . (3) Because long-term prescribed fire alters habitat, it also affects the microclimate at these sites.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of A . phagocytophilum infection in wild red deer varies widely across Europe, from 1.5% in Austria, 10.9% in Portugal, 40–75% in Italy, 80.8% in Spain, and 97.9 to 100% in central Europe (respectively in Slovakia and Hungary) [1521]. Captive deer are probably less prone to tick bites than wild deer due to grazing area management.…”
Section: Discussionmentioning
confidence: 99%